Utilização de filtros grosseiros para remoção de algas presentes em efluentes de lagoas de polimento - Juliana Goncalves Barroso de Andrada (2005)
The research investigates the efficiency of the removal of algae in rock filters for polishing ponds effluent. The system is composed of a UASB reactor followed by two polishing ponds in series and two polishing ponds in parallel. In the end of each one (polishing ponds in parallel) were included rock filters (Filter 1 with grain sizes predominantly in the range of 25 38 mm and the Filter 2 with rocks greater than 76 mm). The rock filters promoted an important additional removal of organic matter completing the removal made by UASB reactor and the polishing ponds. The average concentrations of BOD and COD were 27 and 97 mg/L in Filter 1 and 32 and 107 mg/L in Filter 2, respectively. The average efficiencies of removal of BOD and COD were 37 and 46% in the Filter 1 and 16 and 38% in Filter 2, respectively. The experimental data show that the system can promote a significant removal of SS. The average concentrations of SS in Filter 1 and Filter 2 were 26 and 50 mg/L and the average removal efficiencies were 73 and 48%, respectively. The global efficiencies of removal of E. coli in the system were 5,68 log-units in Filter 1 and 5,82 log-units in Filter 2, corresponding to 99,99979% and 99,99985%, respectively.